Spatial variation of self-containment and jobs-housing balance in Shenzhen using cellphone big data. (April 2018) - Zhou, Xingang; Yeh, Anthony G.O.; Yue, Yang
Abstract: Self-containment of employment and jobs-housing balance have been used to examine commuting patterns from different perspectives. Appropriate jobs-housing ratio may achieve high self-containment. However, self-containment may be affected by other factors. In this study, the spatial variation of self-containment of employment and jobs–housing balance is examined with job types, location, and housing prices using the cellphone data in Shenzhen, China. Jobs–housing balance is found to be more important in self-containment of employment for secondary-sector workers compared with that for tertiary-sector workers. Secondary-sector workers tend to reside near their workplaces because of relatively balanced jobs and housing, whereas tertiary-sector workers tend to reside farther away from their workplaces to save housing cost. The study enhances our understanding of self-containment of employment and jobs-housing balance which is primarily based on Western cities. Highlights: Cellphone data provide more detailed spatial variation of self-containment and jobs-housing balance with a larger sample size than travel survey. Other factors including job types and housing prices can affect the relationship between jobs-housing balance and self-containment of employment.